The favorite grandparents from the perception of preadolescents in Armenia city (Revista de Investigaciones Universidad del Quindío, 2009)
This research forms a part of the studies on Grandparenthood, developed by the Group of Research on Development from the University of Quindío. The figure of the favorite grandparent is described, from the perception of preadolescents in the city of Armenia, from characteristics of the grandparent (age, sex, family of origin, occupation, geographical location and frequency of contact) and how it changes depending on the characteristics of the grandchild. The sample was comformed by 600 preadolescents from different educational institutions, to whom we applied an instrument on the relation grandparentgrandchild. The data was processed in Stadistical Product and Service Solutions (SPSS). Descriptive statistics was used in the identification of the favorite grandparent, and for establishing significant differences in function of the characteristics of the grandchild, the Chi-square and the test U of Mann Whitney.The results indicate that the grandchildren chose their grandmothers as their favorite grandparent (81.4 %), on the mother family (62.1 %), between 60 and 70 years old (43.8 %), who are pensioners or housewives (72.8 %), live in the same city that her grandsons (32.7 %), and see them almost every day (47.4 %).It was found that the characteristics of the figure of the grandparent present variations depending on characteristics of the preadolescent. This way, the age of the favorite grandparent changes in agreement with the familiar structure and the order of birth of the grandchild, when the mother works, the grandsons prefer in major proportion the mother grandmother; the geographical distance and the frequency of contact between favorite grandparents and grandsons change depending on the familiar structure, the number of brothers and the order of birth of the preadolescent.
Keywords: intergenerational Relations; perception of the favorite grandfather